1993
DOI: 10.1111/j.1748-1716.1993.tb09571.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperoxia on bronchial wall dimensions and lung mechanics in rats

Abstract: The effects of exposure to hyperoxic conditions (> 95 kPa at normobaric pressure) on bronchial wall dimensions and lung mechanics were examined in adult rats. Measurements of baseline pulmonary resistance and changes in pulmonary resistance following acetylcholine aerosol inhalation were made in rats exposed to hyperoxia for 48 and 60 h and in control rats exposed to air. Exposures for 48 h were carried out in humid (80% relative humidity) or dry (35-40% relative humidity) conditions. Morphometric measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In animals inspiratory hypoxia has a direct impact on the tone of bronchial smooth muscles resulting in an increase in airway resistance (D'Brot and Ahmed 1991;Dewachter et al 1992), whereas inspiratory hyperoxia induced slight bronchodilation (D'Brot and Ahmed 1991;Libby et al 1981;Murchie et al 1993). In healthy subjects, a slight hypoxia-induced increase in airway resistance was observed whereby pronounced inter-individual differences were found (Dillard et al 1998;Saunders et al 1977;Teague et al 1988).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In animals inspiratory hypoxia has a direct impact on the tone of bronchial smooth muscles resulting in an increase in airway resistance (D'Brot and Ahmed 1991;Dewachter et al 1992), whereas inspiratory hyperoxia induced slight bronchodilation (D'Brot and Ahmed 1991;Libby et al 1981;Murchie et al 1993). In healthy subjects, a slight hypoxia-induced increase in airway resistance was observed whereby pronounced inter-individual differences were found (Dillard et al 1998;Saunders et al 1977;Teague et al 1988).…”
Section: Discussionmentioning
confidence: 92%
“…Inspiratory hypoxia has impact on the tone of the bronchial smooth muscles resulting in hypoxia-induced bronchoconstriction accompanied by an increase in airway resistance (D'Brot and Ahmed 1991;Dewachter et al 1992;Saunders et al 1977;Teague et al 1988) and, conversely, inspiratory hyperoxia reduces the hypoxiainduced increase in pulmonary resistance (D'Brot and Ahmed 1991;Murchie et al 1993). This study followed changes in blood gases in arterialized capillary blood and lung function in CF patients under moderate inspiratory isocapnic hypoxia by hypobaric conditions.…”
Section: Introductionmentioning
confidence: 93%
“…70 In a similar model, smooth muscle expansion is evident after 5 days exposure to hyperoxia, although the epithelial area is unaffected. 70 In a similar model, smooth muscle expansion is evident after 5 days exposure to hyperoxia, although the epithelial area is unaffected.…”
Section: Onset Of Airway Wall Remodellingmentioning
confidence: 96%
“…Using hyperoxia as a stimulus, 48-60 h exposure to > 95 kPa O2 in relatively dry air conditions (approximately 35-40% humidity) causes an increase in the volume occupied by the epithelium in Sprague-Dawley rats. 70 In a similar model, smooth muscle expansion is evident after 5 days exposure to hyperoxia, although the epithelial area is unaffected. 71 Studies in immature (21-day-old) Sprague-Dawley rats have shown that hyperoxia stimulates an expansion in volume occupied by both epithelial and smooth muscle after only 6 days exposure.…”
Section: Onset Of Airway Wall Remodellingmentioning
confidence: 96%
“…It may also be possible that dry normobaric oxygen is more deleterious to lung surface tension than humidified oxygen in the anesthetized dog after 12 h (11). Exposure of rats to dry normobaric oxygen for 48 h caused epithelial thickening in the lobar bronchi, which was not the case with humidified oxygen (12). In patients treated daily with 256 kPa of oxygen for 95 min, humidified oxygen increased the forced expiratory volume in the first second as opposed to dry oxygen (13).…”
mentioning
confidence: 90%